PERFORMANCE ANALYSIS OF SHARIA BANKING IN INDONESIA AND MALAYSIA USING THE SHARIA MAQASHID INDEX CONCEPT (Comparative Study on Sharia Banking in Indonesia and Malaysia 2015-2019 Period) - Rianto; M. Fahruddin; Ameilia Damayanti; Tia Ichwani (INQUISITIVE : International Journal of Economic, 2022)
Abstract: This study aimed to know whether or not there are significant differences between Indonesian’s and Malaysian’s Sharia banks and analyze the performance based on the concept of Maqashid Syariah using SMI (Sharia Maqashid Index) Value. This study is used data from financial report and annual report which were provided by each Islamic Bank sample. The whole samples is consist of 6 Sharia banks in Indonesia and 9 Sharia banks in Malaysia using purposive sampling methods. The total observation is 75 during five years period (2015-2019). The analytical method in this study is Descriptive Test, Normality Test, Homogeneity Test, and Different Test. Based on the results of the study, it can be concluded that the highest-ranking performance of Sharia banking in Indonesia is achieved by BTPN Syariah and the highest-ranking performance of Sharia banking in Malaysia is achieved by CIMB Islamic Bank Berhad. The result of this study showed that SMI Values in Indonesian’s Sharia banking were significantly different to Malaysia’s Sharia banking. Keywords: Maqashid Sharia, Banking Performance, Sharia Banking, Sharia Maqashid Index, Indonesia, Malaysia